Mixed convective fully developed flow in a vertical channel in the presence of thermal radiation and viscous dissipation - Prasad, Kerehalli Vinayaka; Mallikarjun, P.; Vaidya, Hanumesh (Zielona Góra: Uniwersytet Zielonogórski)
The effect of thermal radiation and viscous dissipation on a combined free and forced convective flow in a vertical channel is investigated for a fully developed flow regime. Boussinesq and Roseseland approximations are considered in the modeling of the conduction radiation heat transfer with thermal boundary conditions (isothermal-thermal, isoflux-thermal, and isothermal-flux). The coupled nonlinear governing equations are also solved analytically using the Differential Transform Method (DTM) and regular perturbation method (PM).
Keywords: mixed convection; thermal radiation; viscous dissipation; Differential Transform Method (DTM); Perturbation Method (PM)